Gender-focused analysis and opportunities for upgrading within Vietnam's smallholder pig value chains - Nguyen-Thi-Duong, Nga; Pham-Van, Hung; Duong-Nam, Ha; Nguyen-Thi-Thu, Huyen; Ninh-Xuan, Trung; Dang-Xuan, Sinh; Unger, Fred; Nguyen-Viet, Hung; Grace, Delia (Frontiers in Veterinary Science, 2022)
Gender influences participation in food value chains (VCs) with implications for VC upgrading. This study investigated roles as well as differences in production activities, awareness, training, and attitudes between men and women in Vietnam’s smallholder pig VCs. Data were gathered from a survey of 1,014 actors in different nodes along the chain, and the results showed that both men and women participated in all nodes of the VCs. Women were mainly in charge of routine husbandry activities (e.g., preparing feed, feeding animals, and cleaning pig pens) and participated in input supply (34.7%), pig production (60.2%), pork processing (63.6%), retailing (93.1%), and home preparation and cooking (100%). Men were more often responsible for tasks requiring strength, knowledge, and skills (e.g., disease management) and had greater involvement in larger-scale farming (60-80%) and slaughtering activities (98.0%). Selling of pigs was handled by both genders, but mainly men (73-80%), especially in larger farms. Likely challenges for upgrading pig VCs include limited training for producers, low concern for occupational health risks in all nodes, and misperceptions about food safety. In general, this study found no clear evidence of perceived gender inequality in the smallholder pig VCs in lowland Vietnam. Gendered upgrading in pig VCs should focus on improving women’s ability to access veterinary services and animal disease management and on educating relevant VC actors about occupational health risks.